Superfine nano platinum black catalyst with three-dimensional self-supporting structure as well as preparation method and application of superfine nano platinum black catalyst
By using the preparation method of ultrafine nanoplatinum black catalyst with a three-dimensional self-supporting structure, the combination of platinum salt, inorganic polymerization inhibitor and alkaline solution is used to solve the problem of insufficient efficiency attenuation and mass transfer performance of platinum black catalyst in high temperature scenarios, achieving the effects of high activity, durability and excellent mass transfer performance, while simplifying the preparation process and reducing production costs.
Patent Information
- Application Number
- CN202510074431.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing platinum black catalysts have problems of insufficient efficiency attenuation and mass transfer performance in high temperature and high output power scenarios, and their preparation methods are complex and difficult to mass production.
Using the preparation method of the ultrafine nanoplatinum black catalyst with a three-dimensional self-supporting structure, a platinum salt is mixed with a water-soluble inorganic polymerization inhibitor and an alkaline solution, and dried, heat-treated and dispersed and washed to form a three-dimensional network structure interwoven by platinum nanowires.
The catalyst is achieved with high activity, durability and excellent mass transfer properties, while simplifying the preparation process, reducing production costs and easy mass production.
Smart Images

Figure CN119890327A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure and a preparation method and application thereof. Background Art
[0002] In recent years, fuel cell technology and electrolyzer technology have received widespread attention, but due to the slow kinetics of the electrochemical reactions involved, catalysts must be used to increase the reaction rates. Among them, platinum-based catalysts have shown good practical prospects due to their excellent catalytic performance. Platinum black catalyst, as a non-supported material, is one of the commonly used platinum-based catalysts. Compared with other supported platinum-based catalysts (such as carbon-supported platinum catalysts), platinum black catalysts have a higher tolerance to operating temperatures, can operate at high voltages, and exhibit good stability due to the absence of carbon carriers. Therefore, platinum black catalysts are widely used in scenarios with high temperatures, high output powers, and extremely high requirements for catalyst stability. However, due to the lack of dispersion and anchoring effect of the carrier, platinum black catalysts are prone to coarsening and agglomeration under actual working conditions, resulting in a decrease in catalyst efficiency. In addition, platinum black catalysts are generally composed of nearly spherical nanoparticles of about a few nanometers. Therefore, the porosity of the catalytic layer made of platinum black catalysts is relatively low, which brings serious mass transfer problems. Especially in the high current density area (i.e., concentration polarization area), the mass transfer process of oxygen seriously restricts the output performance of the battery. The above are the two major difficulties faced by the industry in the development of platinum black catalysts.
[0003] During the synthesis of platinum black catalysts, platinum nanoparticles are prone to agglomeration in the absence of a carrier’s dispersing effect. In order to control the size of platinum particles, developers often add additives for protection during the synthesis, but organic additives (such as polyvinyl pyrrolidone, ethylene glycol, sodium citrate, polyether alcohol, etc.) are easily coated on the surface of platinum particles and are still difficult to completely remove after dissolution and washing. When the size of platinum particles is too large or there are adsorbates on the platinum surface, the number of active sites exposed by the catalyst will be reduced, thereby affecting the catalyst activity. Therefore, the selection of synthesis methods, raw materials, and additives are the decisive factors affecting the performance of platinum black catalysts, and the batch preparation of platinum black catalysts is even more challenging.
[0004] Currently, there are few public reports on the preparation method of platinum black catalyst.
[0005] The patent document with publication number CN110124664B discloses that platinum salt is coordinated and complexed with ammonia water, nitrate is added and stirred to obtain a suspension, rotary evaporation is dried, then calcined in air, washed with water and dried, and then reduced in a mixed hydrogen atmosphere to prepare metal platinum black nanoclusters. The method includes two high-energy consumption steps (high-temperature calcination and temperature reduction), which further increases the preparation cost. In the first stage, platinum is calcined in air to oxidize platinum to metal oxide, washed with water to remove impurities, and then subjected to high-temperature heat treatment in a reducing atmosphere. In the absence of a protective agent, there may be a sintering problem.
[0006] Patent document with publication number CN104416164B discloses obtaining platinum black by ultraviolet irradiation and calcination of chloroplatinic acid. This method uses a sacrificial carbon medium to obtain platinum black with a particle size of ~10 nm, wherein the sacrificial substance is g-C3N4 (graphitized carbon nitride, a calcination product of urea). The preparation and calcination removal of the carbon medium undoubtedly increases the process cost, and the uniform dispersion of platinum and the carbon medium is particularly difficult to control during mass production.
[0007] The patent document with publication number CN102794171B discloses a method for preparing platinum black / platinum ruthenium black nano-electrocatalyst, including the synthesis of catalyst precursor-metal carbonyl cluster, injection of magnesium oxide, heat treatment of catalyst intermediate, dissolution of magnesium oxide and catalyst post-treatment steps. The method uses a sacrificial magnesium oxide carrier method to obtain a catalyst particle size between 2nm and 20nm, but removing magnesium oxide and etching with an acid solution will damage the active components of the catalyst. Summary of the invention
[0008] Based on the problem that the current platinum black catalyst cannot simultaneously take into account the high activity, high stability and good mass transfer performance of the catalyst, and the preparation method is complicated and difficult to mass produce, the purpose of the present invention is to provide a three-dimensional self-supporting structure of ultrafine nano platinum black catalyst and its preparation method and application. The catalyst exhibits excellent catalytic activity, durability and mass transfer performance. At the same time, the preparation method has a simple process flow, low production cost, and is easy to mass produce.
[0009] The present invention is achieved through the following technical solutions:
[0010] In a first aspect, the present application provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, comprising the following steps:
[0011] S1, dissolving a platinum salt in water to obtain a first solution; adding a water-soluble inorganic inhibitor to the first solution, and stirring and mixing at a first temperature to obtain a second solution; adding an alkaline solution to the second solution, and stirring and mixing at a second temperature to obtain a third solution;
[0012] S2, drying the third solution to obtain a precursor powder;
[0013] S3, placing the precursor powder in a reducing atmosphere, and performing heat treatment at a third temperature to obtain a catalyst semi-finished product;
[0014] S4. Soak the semi-finished catalyst obtained in step S3 in a small molecule alcohol aqueous solution, disperse, wash and dry to obtain a platinum black catalyst.
[0015] In the second solution of step S1, the platinum salt and the inorganic inhibitor are uniformly mixed in the solution. After drying in step S2, the platinum salt and the inorganic inhibitor form a completely uniform solid powder. In the high-temperature heat treatment of step S3, the inorganic inhibitor remains in a solid state and becomes a physical barrier, which can protect the platinum salt, avoid the problems of pyrolysis loss, structural collapse and sintering of the platinum salt during the high-temperature reduction reaction, inhibit the aggregation and growth of platinum particles, and improve the catalyst yield. In addition, the inorganic inhibitor is very soluble in water, and after dissolution, a large number of pores can be generated and a large specific surface area can be provided, thereby improving the mass transfer efficiency in the catalytic reaction.
[0016] In the third solution of step S1, the platinum salt is mixed with the alkaline solution, and the Pt(IV) in the platinum salt gradually coordinates and complexes with the hydroxyl group to make the platinum salt in the solution evenly dispersed. At the same time, an alkaline solution is added to adjust the pH to prevent the acidic solution from corroding the metal parts in the equipment. The inorganic inhibitor is mixed with the platinum salt and the alkaline solution. In addition to the spatial confinement effect, the inorganic inhibitor also acts as a structural template and pore-forming agent, laying the foundation for the three-dimensional self-supporting structure in the synthesis of platinum black.
[0017] The purpose of heat treatment in step S3 is mainly to reduce the platinum salt to nano-platinum black. At the same time, the reduction temperature cannot be higher than the melting point and decomposition temperature of the inorganic inhibitor. Using inorganic compounds as inhibitors can prevent the aggregation of nano-platinum black and exert a steric hindrance effect.
[0018] In step S4, the dispersion washing is to disperse the semi-finished catalyst in deionized water, perform multiple washing and solid-liquid separation until the conductivity of the washing liquid is ≤10μS / cm; the semi-finished catalyst is evenly dispersed in deionized water, and the dispersion method includes one or a combination of stirring and ultrasound.
[0019] In step S4, the catalyst semi-finished product is immersed in a small molecule alcohol aqueous solution. The inorganic inhibitor is easily soluble in water. After dissolution, a large number of pores and a large specific surface area can be generated, thereby improving the mass transfer efficiency in the catalytic reaction. The small molecule alcohol has a strong non-polarity and is more conducive to carrying impurity ions in and out of the pores, thereby increasing the washing and purification efficiency.
[0020] Furthermore, the platinum salt in step S1 is a water-soluble platinum-containing compound, including any one of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, and sodium chloroplatinite.
[0021] Furthermore, the water-soluble inorganic inhibitor in step S1 is an inorganic compound, including any one or more combinations of potassium chloride, sodium chloride, potassium bromide, and sodium bromide.
[0022] Furthermore, the alkaline solution in step S1 includes an aqueous solution with any one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate as a solute, and the concentration of the alkaline solution is 0.2 mol / L to 8 mol / L.
[0023] Furthermore, the concentration of the alkaline solution is preferably 0.5 mol / L to 5 mol / L.
[0024] Furthermore, in the first solution, the mass ratio of the platinum content in the platinum salt to water is 1:(10-200).
[0025] Furthermore, in the second solution, the mass ratio of the platinum content in the platinum salt to the inorganic inhibitor is 1:(5-80).
[0026] Furthermore, in the third solution, the molar ratio of the alkaline solute to platinum in the alkaline solution is (1-10): (0.5-1).
[0027] Furthermore, in step S2, the drying process is performed by spray drying or freeze drying;
[0028] The spray drying has an inlet temperature of 150°C to 180°C, an outlet temperature of 70°C to 90°C, and a drying air flow rate of 0.5 m 3 / min~3.5m 3 / min, spray air pressure is 120kPa~250kPa;
[0029] The freeze drying is divided into three sections, including one section freezing, two sections sublimation drying, and three sections analytical drying; in the one section program, the temperature is -60°C to -25°C, and the insulation time is 4h to 24h; in the two section program, the temperature is -20°C to -5°C, and the insulation time is 4h to 24h; in the three section program, the temperature is 40°C to 85°C, and the insulation time is 2h to 12h.
[0030] Spray drying can keep the proportions of various components in several small droplets consistent during atomization drying, and freeze drying can quickly fix the components in the solution, including inorganic inhibitors and platinum salts, to prevent them from shifting during other solid-liquid separation or drying methods, so that the components always remain uniform and stable, thereby avoiding the agglomeration and growth of catalyst particles or uneven particle size during subsequent heat treatment.
[0031] Furthermore, the reducing atmosphere in step S3 is a mixture of a reaction gas and a balance gas; the reaction gas includes any one of hydrogen, ammonia, and carbon monoxide; the balance gas includes any one of nitrogen and argon; the volume ratio of the reaction gas to the mixed gas in the reducing atmosphere is 1% to 15%.
[0032] Furthermore, the first temperature is 10°C to 90°C; the second temperature is 10°C to 90°C; the third temperature is 80°C to 450°C; and the temperature of the small molecule alcohol aqueous solution is 50°C to 90°C.
[0033] Among them, the first temperature is preferably 25℃~60℃, the stirring time is 0.2h~3h, preferably 0.5h~1h; the second temperature is preferably 25℃~60℃, the stirring time is 0.5h~18h, preferably 2h~6h; the third temperature is preferably 150℃~400℃, the heat treatment time is 0.5h~6h, preferably 1h~4h, and the heating rate of the heat treatment is 2℃ / min~10℃ / min.
[0034] Furthermore, the small molecule alcohol includes any one or more combinations of ethanol, n-propanol, and isopropanol; the concentration of the small molecule alcohol aqueous solution is 0.5 mol / L to 5 mol / L, preferably 0.8 mol / L to 2.0 mol / L.
[0035] In a second aspect, the present application provides an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, which is prepared using the above-mentioned preparation method.
[0036] Furthermore, the platinum nanowires are intertwined to form a three-dimensional network with a porous structure and a large specific surface area.
[0037] In a third aspect, the present application provides an application of the above-mentioned three-dimensional self-supporting structured ultrafine nano-platinum black catalyst, which is applied in the field of electrochemistry, including for the preparation of fuel cells or electrolyzers.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The platinum black catalyst prepared by the present invention has a regularly arranged three-dimensional self-supporting structure, and the platinum nanowires are intertwined to form a three-dimensional network with rich pore structure and large specific surface area.
[0040] (2) The platinum black catalyst prepared by the present invention has a three-dimensional self-supporting structure. Different from nanoparticles and nanoclusters of platinum black, the unique three-dimensional network structure has enhanced stability, which is conducive to accelerating charge transfer, exposing more active sites, and exhibiting excellent catalytic activity and durability.
[0041] (3) The platinum black catalyst prepared in the present invention can effectively enhance the diffusion of liquids and the transmission of gases. As an electrocatalyst, it exhibits excellent mass transfer performance in the high current density region.
[0042] (4) In the preparation method of the platinum black catalyst of the present invention, an alkaline solution is added to coordinate and complex the Pt(IV) in the platinum salt with the hydroxyl group to make the platinum in the solution evenly dispersed, which lays a good foundation for the ultrafine nanostructure of the platinum black. At the same time, the alkaline solution can adjust the pH of the system to prevent the system from being too acidic and causing corrosion to the metal accessories in the equipment.
[0043] (5) In the preparation method of the platinum black catalyst of the present invention, the platinum salt is mixed with an inorganic inhibitor. During the high-temperature heat treatment, the inorganic inhibitor remains in a solid state and becomes a physical barrier, which can protect the platinum salt and avoid problems such as pyrolysis loss, structural collapse and sintering of the platinum salt during the high-temperature reduction reaction. The agglomeration and growth of platinum particles are inhibited, and the catalyst yield is improved. In addition to the spatial confinement effect, the inorganic inhibitor also acts as a structural template agent and a pore-forming agent, laying the foundation for a three-dimensional self-supporting structure in the synthesis of platinum black.
[0044] (6) The inorganic inhibitor used in the present invention is very soluble in water. After dissolution, it can generate a large number of pores and provide a large specific surface area, thereby improving the mass transfer efficiency in the catalytic reaction.
[0045] (7) The inorganic inhibitor in the present invention can be removed directly by washing with water, thus avoiding the use of chemical reagents to etch the water-insoluble template after thermal decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0047] Figure 1 This is a transmission electron microscope (TEM) image of the platinum black catalyst prepared in Example 1 of the present invention;
[0048] Figure 2 This is a scanning electron microscope image (SEM) of the platinum black catalyst prepared in Example 1 of the present invention;
[0049] Figure 3 This is a scanning electron microscope image (SEM) of the platinum black catalyst prepared in Comparative Example 1 of the present invention;
[0050] Figure 4 This is a scanning electron microscope image (SEM) of the platinum black catalyst prepared in Comparative Example 5 of the present invention;
[0051] Figure 5 The nitrogen physical adsorption / desorption isotherm curves of the platinum black catalysts prepared in Examples 1 to 5 of the present invention;
[0052] Figure 6 The pore size distribution curve of the platinum black catalyst prepared in Examples 1 to 5 of the present invention;
[0053] Figure 7 X-ray diffraction analysis patterns (XRD) of platinum black catalysts prepared in Example 1 and Comparative Examples 1, 2 and 4 of the present invention;
[0054] Figure 8 X-ray diffraction analysis patterns (XRD) of platinum black catalysts prepared in Example 2 of the present invention and Comparative Examples 6, 7 and 9;
[0055] Fig. 9 CV curves of the platinum black catalysts prepared in Example 1 and Comparative Example 1 of the present invention measured before and after the accelerated durability test experiment;
[0056] Fig.10 The performance curves of the platinum black catalyst prepared in Example 1 of the present invention and Comparative Example 1 were measured before and after the fuel cell durability test experiment. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0058] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.
[0059] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" that appear in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. In addition, those skilled in the art will be able to combine and combine different embodiments or examples described in this specification and features of different embodiments or examples, without contradicting each other.
[0060] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0062] Example 1
[0063] This embodiment provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, wherein the mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor is 1:60:15. The specific preparation method is:
[0064] S1. Weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 152 g of deionized water to obtain a first solution; add 37.90 g of sodium chloride to the first solution, and stir for 0.5 h at 60 ° C to obtain a second solution; add 55 mL of 0.5 mol / L sodium hydroxide solution to the second solution, and continue stirring for 3 h at 60 ° C to obtain a third solution.
[0065] S2. The third solution obtained in step S1 is freeze-dried to obtain a precursor powder.
[0066] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 180°C for 2h to obtain a catalyst semi-finished product.
[0067] S4. Soak the catalyst semi-finished product obtained in step S3 in 1.0 mol / L ethanol aqueous solution at 80° C. for 60 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0068] The resistivity of the ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure of Example 1 was tested by a four-probe method, and the result was 0.00297 Ω·cm.
[0069] The nitrogen physical adsorption / desorption isotherm and pore size distribution curve of Example 1 are as follows: Figure 5 and 6 As shown in the figure, an obvious hysteresis loop can be observed at high partial pressures in this isotherm, indicating that the presence of large mesopores in the sample can effectively enhance the diffusion of gas and the transmission of liquid, thereby improving the mass transfer performance. Example 1 has a high specific surface area and pore volume, which are 67.93 m 2 / g and 0.35cm 3 / g.
[0070] The morphology of the platinum black in Example 1 was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 and 2 It can be seen that at the microscopic level, it presents a three-dimensional network composed of interwoven nanowires with a loose porous structure, uniform dispersion and no densely stacked areas. The diameter of the nanowires is about 3nm.
[0071] Example 2
[0072] This embodiment provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, wherein the mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor is 1:100:30. The specific preparation method is:
[0073] S1. Weigh sodium chloroplatinate powder containing 2.53 g of platinum, dissolve it in 253 g of deionized water to obtain a first solution; add 75.80 g of sodium chloride to the first solution, and stir for 0.5 h at a temperature of 60 ° C to obtain a second solution; add 35 mL of a 1.0 mol / L sodium carbonate solution to the second solution, and continue stirring for 3 h at a temperature of 60 ° C to obtain a third solution.
[0074] S2. The third solution obtained in step S1 is freeze-dried to obtain a precursor powder.
[0075] S3. Place the precursor powder obtained in step S2 in a 5% H2 / Ar reducing atmosphere and heat treat it at 200°C for 2h to obtain a catalyst semi-finished product.
[0076] S4. Soak the catalyst semi-finished product obtained in step S3 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0077] The resistivity of the ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure of Example 2 was tested by a four-probe method, and the result was 0.00352 Ω·cm.
[0078] The nitrogen physical adsorption / desorption isotherm and pore size distribution curve of Example 2 are as follows: Figure 5 and 6 As shown in the figure, an obvious hysteresis loop can be observed at high partial pressures in this isotherm, indicating that the presence of large mesopores in the sample can effectively enhance the diffusion of gas and the transmission of liquid, thereby improving the mass transfer performance. Example 2 has a high specific surface area and pore volume, which are 70.58 m 2 / g and 0.34cm 3 / g.
[0079] Example 3
[0080] This embodiment provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, wherein the mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor is 1:60:10. The specific preparation method is:
[0081] S1. Weigh potassium chloroplatinite powder containing 2.53 g of platinum, dissolve it in 152 g of deionized water to obtain a first solution; add 24.85 g of potassium chloride to the first solution, and stir for 2 h at a temperature of 75 ° C to obtain a second solution; add 28 mL of a 1.0 mol / L potassium carbonate solution to the second solution, and continue stirring for 4 h at a temperature of 75 ° C to obtain a third solution.
[0082] S2. The third solution obtained in step S1 is spray-dried to obtain a precursor powder.
[0083] S3. Place the precursor powder obtained in step S2 in a 3% H2 / Ar reducing atmosphere and heat treat it at 150°C for 4 hours to obtain a catalyst semi-finished product.
[0084] S4. Soak the catalyst semi-finished product obtained in step S3 in a 0.8 mol / L n-propanol aqueous solution at 90° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and freeze-dry to obtain a platinum black catalyst.
[0085] The resistivity of the ultrafine nano-platinum black with a three-dimensional self-supporting structure in Example 3 was tested by a four-probe method, and the result was 0.00287 Ω·cm.
[0086] The nitrogen physical adsorption / desorption isotherm and pore size distribution curve of Example 3 are as follows: Figure 5 and 6 As shown in the figure, an obvious hysteresis loop can be observed at high partial pressures in this isotherm, indicating that the presence of large mesopores in the sample can effectively enhance gas diffusion and liquid transport, thereby improving mass transfer performance. Example 3 has a high specific surface area and pore volume, which are 60.08 m 2 / g and 0.33cm 3 / g.
[0087] Example 4
[0088] This embodiment provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, wherein the mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor is 1:60:15. The specific preparation method is:
[0089] S1. Weigh 8.25 g of chloroplatinic acid powder containing platinum, dissolve it in 495 g of deionized water to obtain a first solution; add 123.60 g of sodium chloride to the first solution, and stir for 0.5 h at a temperature of 85 ° C to obtain a second solution; add 280 mL of a 0.5 mol / L sodium hydroxide solution to the second solution, and continue stirring for 6 h at a temperature of 25 ° C to obtain a third solution.
[0090] S2. The third solution obtained in step S1 is freeze-dried to obtain a precursor powder.
[0091] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 400°C for 3 hours to obtain a semi-finished catalyst product.
[0092] S4. Soak the catalyst semi-finished product obtained in step S3 in 0.8 mol / L ethanol aqueous solution at 90° C. for 30 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0093] The resistivity of the ultrafine nano-platinum black with a three-dimensional self-supporting structure of Example 4 was tested by a four-probe method, and the result was 0.00322 Ω·cm.
[0094] The nitrogen physical adsorption / desorption isotherm and pore size distribution curve of Example 4 are as follows: Figure 5 and 6 As shown in the figure, an obvious hysteresis loop can be observed at high partial pressures in this isotherm, indicating that the presence of large mesopores in the sample can effectively enhance the diffusion of gas and the transmission of liquid, thereby improving the mass transfer performance. Example 4 has a high specific surface area and pore volume, which are 61.92 m 2 / g and 0.31cm 3 / g.
[0095] Example 5
[0096] This embodiment provides a method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, wherein the inorganic inhibitor uses a combination of potassium chloride and sodium chloride, with a mass ratio of 1:2. The mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor used is 1:145:30. The specific preparation method is:
[0097] S1. Weigh 8.25 g of chloroplatinic acid powder containing platinum, dissolve it in 1200 g of deionized water to obtain a first solution; add 82.80 g of sodium chloride and 165.60 g of potassium chloride to the first solution, and stir for 1 h at a temperature of 90 ° C to obtain a second solution; add 80 mL of a 2.0 mol / L sodium hydroxide solution to the second solution, and continue stirring for 5 h at a temperature of 90 ° C to obtain a third solution.
[0098] S2. The third solution obtained in step S1 is spray-dried to obtain a precursor powder.
[0099] S3. Place the precursor powder obtained in step S2 in a 10% NH3 / N2 reducing atmosphere and heat treat it at 450°C for 6 hours to obtain a catalyst semi-finished product.
[0100] S4. Soak the catalyst semi-finished product obtained in step S3 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and freeze-dry to obtain a platinum black catalyst.
[0101] The resistivity of the ultrafine nano-platinum black with a three-dimensional self-supporting structure of Example 5 was tested by a four-probe method, and the result was 0.00309 Ω·cm.
[0102] The nitrogen physical adsorption / desorption isotherm and pore size distribution curve of Example 5 are as follows: Figure 5 and 6As shown in the figure, an obvious hysteresis loop can be observed at high partial pressures in this isotherm, indicating that the presence of large mesopores in the sample can effectively enhance the diffusion of gas and the transmission of liquid, thereby improving the mass transfer performance. Example 5 has a high specific surface area and pore volume, which are 63.87 m 2 / g and 0.34cm 3 / g.
[0103] Comparative Example 1
[0104] This comparative example provides a method for preparing a granular platinum black catalyst, which is different from Example 1 in that no water-soluble inorganic inhibitor is added in this comparative example. The specific preparation method is:
[0105] S1. Weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 152 g of deionized water; add 55 mL of 0.5 mol / L sodium hydroxide solution, and stir at 60° C. to obtain a mixture.
[0106] S2. Perform freeze-drying treatment to obtain precursor powder.
[0107] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 180°C for 2h to obtain a catalyst semi-finished product.
[0108] S4. Soak the catalyst semi-finished product obtained in step S3 in 1.0 mol / L ethanol aqueous solution at 80° C. for 60 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0109] The morphology of the platinum black of Comparative Example 1 was characterized by scanning electron microscopy (SEM). Figure 3 It can be seen that the coarse platinum particles are tightly stacked to form a disordered structure. No inhibitor is used in the preparation process, which makes the platinum black particles coarse, unevenly dispersed, and easily agglomerated. It is very easy to sinter during the heat treatment process and the structure collapses.
[0110] Comparative Example 2
[0111] This comparative example provides a method for preparing a granular platinum black catalyst, which is different from Example 1 in that the amount of inorganic inhibitor added in this comparative example is relatively small, and the mass ratio of the platinum content in the platinum salt, deionized water, and inorganic inhibitor is 1:60:2. The specific preparation method is:
[0112] S1. Weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 152 g of deionized water; add 5.08 g of sodium chloride, and stir for 0.5 h at a temperature of 60° C. to mix; add 55 mL of a 0.5 mol / L sodium hydroxide solution, and continue stirring for 3 h at a temperature of 60° C. to obtain a mixture.
[0113] S2. Perform freeze-drying treatment to obtain precursor powder.
[0114] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 180°C for 2h to obtain a catalyst semi-finished product.
[0115] S4. Soak the catalyst semi-finished product obtained in step S3 in 1.0 mol / L ethanol aqueous solution at 80° C. for 60 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0116] Comparative Example 3
[0117] This comparative example provides a method for preparing a platinum black catalyst, which is different from Example 1 in that an inorganic inhibitor is added in excess in this comparative example, and the mass ratio of the amount of platinum in the platinum salt, deionized water, and inorganic inhibitor is 1:200:90. The specific preparation method is:
[0118] S1. Weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 506 g of deionized water; add 228 g of sodium chloride, and stir for 0.5 h at 60 ° C; add 55 mL of 0.5 mol / L sodium hydroxide solution, and continue stirring for 3 h at 60 ° C to obtain a mixture.
[0119] S2. Perform freeze-drying treatment to obtain precursor powder.
[0120] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 180°C for 2h to obtain a catalyst semi-finished product.
[0121] S4. Soak the catalyst semi-finished product obtained in step S3 in 1.0 mol / L ethanol aqueous solution at 80° C. for 60 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0122] Comparative Example 4
[0123] This comparative example provides a method for preparing a platinum black catalyst, which is different from Example 1 in that no alkaline solution is used in this comparative example. The specific preparation method is:
[0124] S1. Weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 152 g of deionized water; add 37.90 g of sodium chloride, and stir at 60° C. to obtain a mixture.
[0125] S2. Perform freeze-drying treatment to obtain precursor powder.
[0126] S3. Place the precursor powder obtained in step S2 in a 10% H2 / N2 reducing atmosphere and heat treat it at 180°C for 2h to obtain a catalyst semi-finished product.
[0127] S4. Soak the catalyst semi-finished product obtained in step S3 in 1.0 mol / L ethanol aqueous solution at 80° C. for 60 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0128] Comparative Example 5
[0129] This comparative example provides a method for preparing a nanoclustered platinum black catalyst, wherein ammonia water and sodium nitrate are used in the solution. The specific preparation method is:
[0130] S1. At room temperature, weigh 2.53 g of chloroplatinic acid powder containing platinum, dissolve it in 250 g of deionized water; add 100 mL of 10 mol / L ammonia water dropwise, stir for 5 h; add 100 g of sodium nitrate, stir for 2 h.
[0131] S2. Perform freeze-drying treatment to obtain precursor powder.
[0132] S3. The precursor powder obtained in step S2 is first calcined in air at 400° C. for 2 h to perform platinum oxidation treatment, and then washed and dried to obtain a catalyst semi-finished product.
[0133] S4. Reduce the semi-finished catalyst obtained in step S3 in a 10% H2 / N2 reducing atmosphere at 250°C for 2h to obtain a platinum black nanocluster catalyst.
[0134] The morphology of the platinum black of comparative example 5 was characterized by scanning electron microscopy (SEM). Figure 4 It can be seen that the nanoclustered platinum black is assembled into a slightly compact structure with few pores. This is because in step S4, during the process of reducing platinum by heat treatment, no inhibitor is added for protection. Therefore, nanoclustered or nanoparticle-like platinum black is prone to self-assembly, and even brings the risk of partial sintering.
[0135] Comparative Example 6
[0136] This comparative example provides a method for preparing a platinum black catalyst, which is different from Example 2 in that the third solution in this comparative example adopts another drying method (rotary evaporation followed by vacuum drying). The specific preparation method is:
[0137] S1. Weigh sodium chloroplatinate powder containing 2.53 g of platinum, dissolve it in 253 g of deionized water to obtain a first solution; add 75.80 g of sodium chloride to the first solution, and stir for 0.5 h at a temperature of 60 ° C to obtain a second solution; add 35 mL of a 1.0 mol / L sodium carbonate solution to the second solution, and continue stirring for 3 h at a temperature of 60 ° C to obtain a third solution.
[0138] S2. The third solution obtained in step S1 is subjected to rotary evaporation, vacuum drying, and grinding to obtain a precursor powder.
[0139] S3. Place the precursor powder obtained in step S2 in a 5% H2 / Ar reducing atmosphere and heat treat it at 200°C for 2h to obtain a catalyst semi-finished product.
[0140] S4. Soak the catalyst semi-finished product obtained in step S3 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0141] Comparative Example 7
[0142] This comparative example provides a method for preparing a platinum black catalyst, which is different from Example 2 in that the platinum salt, the polymerization inhibitor and the alkaline substance in this comparative example are not prepared into a uniform solution, but are directly obtained as a solid by mechanical mixing to obtain a powder. The specific preparation method is:
[0143] S1. Weigh sodium chloroplatinate powder containing 2.53 g of platinum, 75.80 g of sodium chloride and 3.71 g of sodium carbonate, grind them manually in an agate mortar for 30 min, and then crush them by high-speed shear for 10 min to obtain a powder with uniform color.
[0144] S2. Place in a 5% H2 / Ar reducing atmosphere and heat treat at 200°C for 2h to obtain a semi-finished catalyst.
[0145] S3. Soak the catalyst semi-finished product obtained in step S2 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0146] Comparative Example 8
[0147] This comparative example provides a method for preparing a platinum black catalyst. The difference from Example 2 is that the heat treatment temperature in this comparative example is relatively low. The specific preparation method is:
[0148] S1. Weigh sodium chloroplatinate powder containing 2.53 g of platinum, dissolve it in 253 g of deionized water; add 75.80 g of sodium chloride, and stir for 0.5 h at a temperature of 60° C.; add 35 mL of a 1.0 mol / L sodium carbonate solution, and continue stirring for 3 h at a temperature of 60° C. to obtain a mixture.
[0149] S2. Perform freeze-drying treatment to obtain precursor powder.
[0150] S3. Place the precursor powder obtained in step S2 in a 5% H2 / Ar reducing atmosphere and keep it at 45°C for 2 hours to obtain a semi-finished catalyst product.
[0151] S4. Soak the catalyst semi-finished product obtained in step S3 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0152] Comparative Example 9
[0153] This comparative example provides a method for preparing a platinum black catalyst. The difference from Example 2 is that the heat treatment temperature in this comparative example is too high. The specific preparation method is:
[0154] S1. Weigh sodium chloroplatinate powder containing 2.53 g of platinum, dissolve it in 253 g of deionized water; add 75.80 g of sodium chloride, and stir for 0.5 h at a temperature of 60° C.; add 35 mL of a 1.0 mol / L sodium carbonate solution, and continue stirring for 3 h at a temperature of 60° C. to obtain a mixture.
[0155] S2. Perform freeze-drying treatment to obtain precursor powder.
[0156] S3. Place the precursor powder obtained in step S2 in a 5% H2 / Ar reducing atmosphere and heat treat it at 1050°C for 2h to obtain a catalyst semi-finished product.
[0157] S4. Soak the catalyst semi-finished product obtained in step S3 in a 1.5 mol / L n-propanol aqueous solution at 85° C. for 50 min, then use deionized water to disperse and wash until the conductivity of the washing liquid is ≤10 μS / cm, and vacuum dry at 60° C. to obtain a platinum black catalyst.
[0158] The performance of the catalysts prepared in the above examples and comparative examples was tested.
[0159] 1. Characterization and analysis of catalyst materials
[0160] The platinum particle size, platinum content and specific surface area of the platinum black catalyst prepared by the present invention were measured using an X-ray diffraction analyzer (XRD), a thermogravimetric analyzer (TG) and a nitrogen physical adsorption instrument. The results are shown in Table 1.
[0161] The microstructure of the platinum black catalyst obtained in Example 1 was characterized by transmission electron microscopy (TEM). Figure 1 shown.
[0162] The dispersion and agglomeration of the platinum black catalysts obtained in Example 1, Comparative Examples 1 and 5 were characterized by scanning electron microscopy (SEM). Figure 2-4 shown.
[0163] 2. Catalyst electrochemical performance test
[0164] Preparation of working electrode: Weigh 3.8 mg of the platinum black catalyst obtained in the present invention and transfer it to a 20 ml glass sample bottle. Then add 7.6 mL of ultrapure water and 2.4 mL of isopropanol, ultrasonically disperse for 30 min, then cool to room temperature, drop 40 μL of 5% Nafion solution, and continue ultrasonication for 10 min to obtain catalyst ink. Apply the ink dropwise on a clean glassy carbon electrode and obtain a working electrode after drying. The platinum loading is: 15 μg / cm 2 In the electrochemical test, a saturated calomel electrode is used as the reference electrode, a graphite electrode is used as the counter electrode, and a three-electrode test system is built.
[0165] Cyclic voltammetry test: Electrochemical activation and cyclic voltammetry (CV) were performed in a nitrogen-saturated 0.1M HClO4 electrolyte. The scanning potential range was 0.05-1.2V vs. RHE (relative reversible hydrogen electrode potential), and the scanning rate was 50mV / s. The standard CV curve was measured and the electrochemical active area (ECSA) was calculated. The results are shown in Table 1.
[0166] Table 1
[0167] Case Platinum particle size (nm) Platinum content (%) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[ECSA(m 2 / g)]]> Example 1 3.50 98.45 67.93 55.94 Example 2 3.21 99.24 70.58 45.91 Example 3 4.33 99.07 60.08 44.57 Example 4 3.84 98.63 61.92 49.53 Example 5 3.81 99.63 63.87 49.19 Comparative Example 1 20.20 90.21 11.63 5.54 Comparative Example 2 12.55 92.08 16.05 9.81 Comparative Example 3 8.57 91.48 25.13 17.30 Comparative Example 4 10.95 95.58 20.44 12.77 Comparative Example 5 2.95 89.52 51.20 30.34 Comparative Example 6 9.27 94.66 23.23 15.69 Comparative Example 7 9.05 96.52 23.80 16.07 Comparative Example 8 7.25 80.56 29.71 15.82 Comparative Example 9 12.57 97.45 16.47 10.46
[0168] Accelerated durability test: Perform electrochemical accelerated aging test in 0.1M HClO4 electrolyte, scan potential range 0.6~0.95Vvs.RHE, scan rate 100mV / s, and perform 30000 CV cycle test. Compare the ECSA changes before and after the durability test (see attached for details). Fig. 9 ).
[0169] 3. Fuel cell performance test
[0170] Preparation of membrane electrode: The catalysts prepared in Example 1 and Comparative Example 5 were sprayed on both sides of the polymer electrolyte membrane to prepare catalyst coated membrane (CCM), and assembled with carbon paper into membrane electrode assembly (MEA) for testing, and IV curves were obtained (see Appendix for details). Fig.10 ). The amount of platinum used (anode / cathode): 0.1 mg cm -2 / 0.3mg·cm -2 .
[0171] Performance test conditions: battery operating temperature: 80°C; relative humidity (anode / cathode): 50% / 50%; reaction gas stoichiometric ratio (anode / cathode): hydrogen 1.2 / oxygen 2.5; back pressure (anode / cathode): 50kPa / 50kPa.
[0172] Endurance cycle test conditions: temperature 75°C; humidity 100% / 100% (anode / cathode); back pressure (anode / cathode) 100 / 100 kPa; flow rate (anode / cathode) 0.2 / 0.8 L / min; square wave cycle: 0.6-0.95 V, each lasting 3 seconds.
[0173] Table 1 is a comparison of the material characterization and performance tests of the platinum black catalysts prepared in the examples and comparative examples. Examples 1-5 all adopt the method described in the present invention: deionized water, platinum salt and inorganic inhibitor are fully mixed in a certain proportion, an alkaline solution is added, and Pt (IV) in the platinum salt is coordinated and complexed with the hydroxyl group to make the platinum in the solution evenly dispersed, and a precursor powder is obtained by spray drying or freeze drying, and then heat-treated, washed and dried to obtain an ultrafine nano platinum black catalyst with a three-dimensional self-supporting structure composed of interwoven platinum nanowires. This highly regularly arranged nanoarray can significantly improve the conductivity of the material, thereby accelerating charge transfer. The average particle size of the obtained platinum black catalyst is between 3 and 5 nm, with a large specific surface area and abundant pores. These characteristics are conducive to providing more active sites and enhancing material transfer, thereby exhibiting a higher active surface area, and showing excellent catalytic activity, durability and mass transfer performance. According to Fig. 9 , comparing the durability tests of Example 1 and Comparative Example 1, after the accelerated aging test, the electrochemical active area of Example 1 was almost not attenuated, while the ECSA of Comparative Example 1 after the cycle test became very small, indicating that the stability and electrochemical performance of the self-supporting structure are more advantageous, and the granular platinum black is easy to agglomerate and grow, and the structural stability is poor; according to Fig.10The fuel cell test results show that Example 1 has a significant performance advantage in the high current density region, indicating that the three-dimensional self-supporting structure is very beneficial to reducing mass transfer impedance. This is because the catalyst layer made of the catalyst with a self-supporting structure can maintain a good porosity, thereby greatly slowing down the performance degradation in the high current density region caused by concentration polarization. At the same time, the potential decay amplitude of Example 1 is smaller than that of Comparative Example 5, further illustrating that the ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure prepared by the present invention has good catalytic activity and durability.
[0174] like Figure 7 As shown, the present invention also provides a comparative example. For the cases where no inorganic inhibitor is used (Comparative Example 1) and the amount of inorganic inhibitor added is low (Comparative Example 2), there is a lack of sufficient physical barriers during high-temperature heat treatment, which leads to easy sintering during the platinum salt reduction reaction, and very few pores left in the catalyst after washing. The precursor powder of Example 1 contains an appropriate amount of inorganic inhibitor and platinum salt, and each component is evenly dispersed, which is conducive to improving the platinum reduction rate. However, in Comparative Examples 1 and 2, due to the lack of the barrier effect of the inorganic inhibitor, the first reduced platinum black may cover part of the platinum salt and affect the internal contact with the reducing atmosphere, thereby resulting in a decrease in yield; similarly, when the inorganic inhibitor is excessive (Comparative Example 3), too much inorganic inhibitor will also wrap part of the platinum salt and affect its full reduction, resulting in a decrease in the platinum reduction rate. Comparative Example 4 does not use alkali solution, and the Pt(IV) of the platinum salt in the solution fails to coordinate and complex with the hydroxyl group. In this case, the average particle size of platinum increases significantly; Comparative Example 5 uses the Pt(IV) in the platinum salt to react with ammonia water, mixes with sodium nitrate, and then oxidizes the platinum by air calcination, and then reduces it to platinum black nanoclusters by secondary heat treatment. In this way, the obtained platinum particle size is small, but the oxidation of platinum and then gas phase thermal reduction increase the preparation energy consumption, the reduction of oxidized platinum is relatively difficult, and the platinum content of the obtained platinum black catalyst is low. In terms of structural stability, the stability of the nanocluster morphology is relatively weaker than that of the three-dimensional self-supporting structure composed of interwoven platinum nanowires. Therefore, the ultrafine nano platinum black catalyst with a three-dimensional self-supporting structure prepared by the present invention shows more excellent durability in the electrochemical accelerated durability test.
[0175] like Figure 8As shown, compared with Example 2, Comparative Example 6 uses rotary evaporation, and Comparative Example 7 directly mechanically mixes the raw material powders for preparing the solution. Both operations will lead to uneven dispersion of platinum salt and inorganic inhibitor in the precursor powder. This is because the solubility difference between platinum salt and inorganic inhibitor leads to different rates and times of raw material precipitation during rotary evaporation, and mechanical mixing is difficult to achieve uniform distribution at the molecular level in the solution. Therefore, when the components in the precursor powder are uneven, the size and uniformity of platinum will definitely be affected. Heat treatment conditions are critical to the platinum reduction process. Compared with Example 2, the heat treatment temperature of Comparative Example 8 is low, which reduces the platinum reduction rate and catalyst yield; the heat treatment temperature of Comparative Example 9 is too high. At a temperature of 1000°C, sodium chloride and platinum salt are in a molten state, and the confinement effect is weakened. As the heat treatment temperature increases, the platinum particle size will increase significantly.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing an ultrafine nano-platinum black catalyst with a three-dimensional self-supporting structure, characterized in that: The following steps are involved: S1, dissolving a platinum salt in water to obtain a first solution; adding a water-soluble inorganic inhibitor to the first solution, and stirring and mixing at a first temperature to obtain a second solution; adding an alkaline solution to the second solution, and stirring and mixing at a second temperature to obtain a third solution; S2, drying the third solution to obtain a precursor powder; S3, placing the precursor powder in a reducing atmosphere, and performing heat treatment at a third temperature to obtain a catalyst semi-finished product; S4. Soaking the catalyst semi-finished product obtained in step S3 in a small molecule alcohol aqueous solution, dispersing, washing and drying to obtain a platinum black catalyst; the platinum nanowires of the platinum black catalyst are intertwined to form a three-dimensional network with a porous structure and a large specific surface area.
2. The method for preparing a three-dimensional self-supporting ultrafine nano-platinum black catalyst according to claim 1, characterized in that: The platinum salt in step S1 is a water-soluble platinum-containing compound, including any one of chloroplatinic acid, potassium chloroplatinate, potassium chloroplatinite, sodium chloroplatinate, and sodium chloroplatinite; The water-soluble inorganic inhibitor in step S1 is an inorganic compound, including any one or more combinations of potassium chloride, sodium chloride, potassium bromide, and sodium bromide; The alkaline solution in step S1 includes an aqueous solution with any one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate as a solute, and the concentration of the alkaline solution is 0.2 mol / L to 8 mol / L.
3. The method for preparing a three-dimensional self-supporting ultrafine nano-platinum black catalyst according to claim 1, characterized in that: In the first solution, the mass ratio of the platinum content in the platinum salt to water is 1:(10-200); in the second solution, the mass ratio of the platinum content in the platinum salt to the inorganic inhibitor is 1:(5-80).
4. The method for preparing a three-dimensional self-supporting structured ultrafine nano-platinum black catalyst according to claim 1, characterized in that: In the third solution, the molar ratio of the alkaline solute to platinum in the alkaline solution is (1-10): (0.5-1).
5. The method for preparing a three-dimensional self-supporting structured ultrafine nano-platinum black catalyst according to claim 1, characterized in that: In step S2, the drying process is performed by spray drying or freeze drying; The spray drying has an inlet temperature of 150°C to 180°C, an outlet temperature of 70°C to 90°C, and a drying air flow rate of 0.5 m 3 / min~3.5m 3 / min, spray air pressure is 120kPa~250kPa; The freeze drying is divided into three sections, including one section freezing, two sections sublimation drying, and three sections analytical drying; in the one section program, the temperature is -60°C to -25°C, and the insulation time is 4h to 24h; in the two section program, the temperature is -20°C to -5°C, and the insulation time is 4h to 24h; in the three section program, the temperature is 40°C to 85°C, and the insulation time is 2h to 12h.
6. The method for preparing a three-dimensional self-supporting structured ultrafine nano-platinum black catalyst according to claim 1, characterized in that: The reducing atmosphere in step S3 is a mixture of a reaction gas and a balance gas; the reaction gas includes any one of hydrogen, ammonia, and carbon monoxide; the balance gas includes any one of nitrogen and argon; the volume ratio of the reaction gas to the mixed gas in the reducing atmosphere is 1% to 15%.
7. The method for preparing a three-dimensional self-supporting structured ultrafine nano-platinum black catalyst according to claim 1, characterized in that: The first temperature is 10°C to 90°C; the second temperature is 10°C to 90°C; the third temperature is 80°C to 450°C; and the temperature of the small molecule alcohol aqueous solution is 50°C to 90°C.
8. The method for preparing a three-dimensional self-supporting structured ultrafine nano-platinum black catalyst according to claim 1, characterized in that: The small molecule alcohol includes any one or more combinations of ethanol, n-propanol, and isopropanol; the concentration of the small molecule alcohol aqueous solution is 0.5 mol / L to 5 mol / L.
9. A three-dimensional self-supporting ultrafine nano-platinum black catalyst, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. The three-dimensional self-supporting ultrafine nano-platinum black catalyst according to claim 9, characterized in that: Including use in preparing fuel cells or electrolyzers.
Citation Information
Patent Citations
Method for preparing platinum black / platinum ruthenium black nano electro-catalyst by using sacrificial magnesia carrier
CN102794171B
Platinum black and its preparation method
CN104416164B
Platinum Black Nanocluster Catalysts and Their Preparation Methods
CN110124664B
Metal platinum black nanocluster catalyst and preparation method thereof
CN110124664A
Preparation method of platinum-carbon catalyst, platinum-carbon catalyst and catalyst coating film
CN115458755A
Cited By
Preparation method of self-assembled porous network platinum
CN120696419A
Method for preparing platinum black catalyst with controllable particle size under assistance of amidine ligand
CN120878871A